FRI0207 Cardiovascular Risk Scoring Systems in Spondyloarthritis. Which One Should We Use?. (9th June 2015) - Alonso Blanco-Morales, E.; Rey, R.; Bravo-Ferrer, J.; Bejerano, C.; Fernández, C.; Oreiro, N.; Gromaz, J.; Raga, A.; Atanes, A.; Freire, M.; De Toro, F.; Blanco, F.; et al.
Abstract : Background: Several studies have described an increased cardiovascular (CV) morbidity and mortality in Spondyloarthritis (SpA) compared to overall population, mainly in Psoriatic Arthritis (PsA) and Ankylosing Spondylitis (AS), secondary to an increase in classic and non-classic cardiovascular risk factors (CVRF), presumably due to chronic inflammation. EULAR recommends the use of local guidelines for CV risk assessment in SpA. Objectives: To estimate the CV risk (CVR) in SpA spanish patients using validated risk scoring systems and to determine which one should we use. Methods: Observational and ambispective study of 410 SpA patients (222 PsA according to CASPAR classification criteria and 188 AS patients according to modified New York classification criteria) belonging to our follow-up cohort (2004-2014). We collected demographic, clinical and laboratory data from their baseline visit. We used the two function charts available in our country (low risk group) for CVR assessment: systematic coronary risk evaluation (SCORE) calibrated for Spain and the Framingham-Registre Gironi del COR (REGICOR). We used Framingham original score too. Patients aged <34 or >74 years, those with history of CV event (CVE) and patients with incomplete data were excluded for the assessment.CVE was defined by ischemic heart disease or stoke. Information on new CVEs were obtained until December 2014. Statistical analysis was performed by SPSS 21.0 program. It was considered p<0.05 as significant. Results: Of the 410 patients, 68.3%, 280 were men, the mean age was 50 (±14) years and the mean duration of disease was 8 (±9) years. Among CVRF: 27.8% active smoker, 6% Diabetes Mellitus, mean waist circumference 96 (±15) cm, mean body mass index 28 (±6), mean total cholesterol, HDL-cholesterol, triglycerides and uric acid were 213 (±6), 60 (±17), 133 (±160) and 5.6 (±1.7) mg/dl respectively. Mean CRP was 1.2 (±1.9) mg /dl. After applying exclusion criteria, CVR assessment was performed in 195 SpA (71 AS and 124 PsA) patients. This subgroup of patients showed no statistically significant differences in baseline characteristics previously described. These were the results of the assessments: Spanish calibrated SCORE 4.8 (±4.8)%, REGICOR 4.3 (±2.8)%, and Framingham 9.8 (±7.1) %. Over a mean follow up of 6 (±2) years, CVE rate was 12%. If we use CVR index as predictor of CVE, in our series, the index with better prediction would be Framingham with an area under the curve of 0.845 (CI 0.778-0-912 p<0.001) with a Sensibility of 100% and Specificity of 57% taking as cut-off a result of 10%. Conclusions: According with other studies, SCORE and Framingham index calibrated for Spain, underestimate the RCV in SpA patients (in our series, without completing the ten years follow-up, the collected CVE duplicate the estimation of both scoring systems). It seems reasonable that we should apply a corrector factor to these score calculators as suggest the EULAR recommendations in Rheumatoid Arthritis. Until this happens, it would be appropriate to apply to these patients the Framingham original score. Disclosure of Interest: None declared